Time management through indoor location - André Costa Teixeira (2021)
Indoor location systems have evolved greatly in recent decades and their importance has progressively grown in various aspects of everyday life, especially in business environments. This dissertation describes the design and evaluation of a possible indoor positioning system to collect data about the assets and personnel of the company RACELAND S.A.. This system uses the iBeacon BLE (Bluetooth Low Energy) technology that enables the identification and collection of the signal strength to determine the distances to the reference points. The main objective is to design a system with sufficient accuracy that it could collect data on the tasks being performed and then evaluate it based on key performance indicators. The work presented here is about a different approach to BLE Beacon devices, which are used as moving targets. The implemented system uses access points, called "gateways", to collect and send the data sent by the beacon cards. Each beacon card will be assigned to an employee or company asset. By collecting the signals received from different access points, it is possible to estimate the position of the beacon. A research of the state of the art in indoor location technologies is made available and a comparison between some of the possibilities or technologies already investigated or present in the market is presented. The theme of location in its various different aspects is explained and issues relating to user privacy and security are discussed. The basic framework for the subject of localization is defined and the fundamental concepts of localization and design are explained. A discussion is also made to address the issues relating to user privacy and security. Then, a presentation of the project to be developed is made, where the requirements and features that the company intends to achieve are defined. The system is modeled and the architecture of the system is described. The development methodology is described, decomposing the steps and tests carried out until reaching the complete system. Once the system is completed, it is evaluated with some metrics and benchmarks. Finally, it ends by exposing what has been achieved, the limitations and what can be done to improve the system.